Externalisation, internalisation ou réinternalisation ? Le cas de l’administration régionale bruxelloise - Jonathan de Wilde d’Estmael; Elise Dermine; Nick Deschacht; Nicola Francesco Dotti; Kelly Huegaerts; Barbara Janssens; Maria Cecilia Trionfetti; Christophe Vanroelen (Brussels Studies, 2020)
Since the 1980s, there has been a trend for businesses and public administrations to focus on their core activities, outsourcing tasks such as IT, security, catering and cleaning services. However, in recent years, many organisations have been reversing the trend by insourcing, or “backsourcing”, some of these activities. The aim of this article is to study the extent to which activities have been outsourced in the Brussels regional administrations, its impact on workers and organisations involved, and the attitudes of stakeholders towards a possible re-internalisation of low-skilled jobs. Based on a multidisciplinary BSI project for Talent.Brussels, our findings show that decisions about outsourcing and insourcing are complex and multidimensional, and that they should not be based solely on monetary cost considerations.